2023
DOI: 10.1108/sampj-10-2021-0401
|View full text |Cite
|
Sign up to set email alerts
|

Influence of distracted mutual fund investors on corporate ESG decoupling: evidence from China

Abstract: Purpose This study aims to explore whether investors’ inattention is associated with firms’ environmental, social and governance (ESG) decoupling, which is defined as the misalignment between the implementation and incorporation of ESG policies. Design/methodology/approach Focusing on a sample of the components of ESG ratings for China Securities Index (CSI) 300 companies between 2017 and 2019, the authors test the relationship between firms’ ESG decoupling level and mutual fund investors’ distraction by app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 109 publications
2
15
0
Order By: Relevance
“…Overall, researchers stressed that CSR decoupling leads to negative corporate financial consequences . This is in line with the business case argument, legitimacy theory and agency theory, assuming a decreased stakeholder trust and lack of firm reputation (Hawn & Ioannou, 2016; Liu et al, 2023). If CSR decoupling behavior is obvious, firms are confronted with increased stakeholder concerns, decreased firm reputation and impaired financial performance.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…Overall, researchers stressed that CSR decoupling leads to negative corporate financial consequences . This is in line with the business case argument, legitimacy theory and agency theory, assuming a decreased stakeholder trust and lack of firm reputation (Hawn & Ioannou, 2016; Liu et al, 2023). If CSR decoupling behavior is obvious, firms are confronted with increased stakeholder concerns, decreased firm reputation and impaired financial performance.…”
Section: Resultssupporting
confidence: 83%
“…Zhao et al (2022) found a positive relationship between board network centrality and greenwashing in the pre‐adoption period of new environmental regulations. Liu et al (2023) documented that mutual fund investors' distraction increases CSR decoupling, more pronounced by negative shocks. Shareholder attendance mediates this relationship.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations